Let's do theology - as in the book of Job: Developing theology in dialogue - V. Kessler (Acta Theologica)
This article demonstrates how the Book of Job might inspire us to do theology in a different way. For nearly two millennia, Christian theology has mainly been presented in monologues, either from the pulpit or in the classroom. The Book of Job offers an alternate way to develop theology – through dialogue. It is argued that the speeches of the three (or four) friends should be valued and viewed as an important part of the Book of Job. The faith-based facilitation (FBF) process, a praxis cycle developed by the Salvation Army, is used as a filter on the Book of Job. The FBF process stresses communal decision-making and the importance of Kairos experiences. It is argued that the Book of Job contains at least two Kairos experiences, the divine speech from the storm and the soft voice in Eliphaz’ first speech, which was unfortunately overheard. The article ends with four conclusions for doing theology nowadays.